(untitled) (Olhar de Professor, 2021)
Abstract: This report aims to share the construction of welcoming’s spaces and meetings with Ipê Amarelo Childhood Education Unit’s early education’s children and their families in this moment of exceptionality experienced by the covid-19’s pandemic. Professionals whose work with children have been asking: what is our role of as a Childhood Education Unit that welcomes children and their families at present context? How do we teachers and professionals whose work with young and very young children maintain bonds that were being built and were abruptly interrupted without the school’s environment and the physical interaction? How the teacher’s sensitive listening can happen in this context? Based on these issues we collective found possibilities and different paths for a group of children and families that we will address at this collaborative writing.